KEPEMIMPINAN TRADISIONAL MASYARAKAT BATAK ANGKOLA DI KERAJAAN LUAT MARANCAR PADA MASA PENDUDUKAN BELANDA DAN JEPANG (1930-1942) - Erwin Siregar; Salman Alparis Sormin (Institut Pendidikan Tapanuli Selatan, 2021)
Problem on this research was funtion and king’s role vanishing in society since paderi invention, Duch and Japan colonization. It brouht a changing to traditional goverment system that has been appropriate to costum and Batak Angkola’s culture. This research was to know that traditional leadhership of Angkola society in Luat Marancar Kingdom before Dutch was coming. Then, it was also to know impact of Dutch and Japan colonization to traditional leadership of Angkola society in Luat Marancar Kingdom. And, it was done in order to know the difference between traditional leadership in Dutch and Japan period in Angkola society in Luat Marancar Kingdom.This research used history method by using primary and secondart sources. Primary sources in this research were kings’ heritance notes who have become a leader in Luat Marancar kingdom, kings’ generation who were still alive till now, and costum figure on that society who were pretened knowing the story of Marancar kingdom. For secondary sources, there were apparatuses regency government, old figures and documents or books that were related to this research. Besides, this research also used interview with some discipline approaches; anthropology, sociology as needed in order to enrich this research.The findings of this research consited of traditional leadership of Marancar Luat society before effect of Dutch was coming, leader or kings’ role and function as leader and costum leader. However, after Dutch Governement came to Luat Marancar, there was a significant changing of leadership concept in Luat Marancar which are kings’ role and fuction changing into Dutch colonization servants in taking tax and controlling hard corvee. While when Japan came, there was no significant changing in government system in Luat Marancar Kingdom.